Analisis Pasar Digital Dalam Pengambilan Keputusan Pembelian Produk Skintific - Ghofar, Khidhir Akbar; Indriyani, Rina; Septiani, Metta (CORISINDO 2025, 2025)
The development of digital technology has significantly changed consumer behavior in purchasing products, especially skincare products such as Skintific. The purpose of this study is to analyze the factors that influence the decision to purchase Skintific in the digital market. The research method used is a quantitative approach with data collection techniques through online surveys of 150 respondents who are product users. Data analysis was conducted using multiple linear regression and market segmentation. The results of the study show that product quality, price, digital marketing, influencer marketing, and customer reviews have a significant impact on purchasing decisions. In addition, market segmentation shows that female platform users in the 18–25 age group are the dominant segment when purchasing products with Shimizu. The company provides strategic effects to improve product quality and strengthen digital marketing and collaboration with influencers as their main marketing strategy.